Role of Angiotensin-Converting Enzyme (ACE) gene polymorphism and ACE activity in predicting outcome after acute myocardial infarction. (February 2021) - Moorthy, Nagaraja; Saligrama Ramegowda, Kalpana; Jain, Simran; Bharath, G.; Sinha, Archana; Nanjappa, Manjunath C.; Christopher, Rita
Highlights: The role of ACE gene polymorphism and its influence on ischemic heart disease and acute coronary syndrome are studied in last so many years without any concrete conclusion. In this study we investigated role of ACE gene polymorphism and Ace activity in large number of study population. The ACE (I/D) polymorphism showed no association with development of acute STEMI. Neither ACE I/D polymorphism nor ACE activity predicted in-hospital mortality in patients admitted with acute STEMI. Hence knowledge of ACE polymorphism and Ace activity is not useful in predicting STEMI or mortality after STEMI. Abstract: Background: The Ace polymorphism had shown association with ACE activity, premature atherosclerosis, myocardial infarction, LV dysfunction, LV remodelling, severity and extent of CAD and mortality after MI. Though ACE I/D polymorphism has been reported to be associated with various cardiovascular diseases it remained a controversial risk factor and studies have presented conflicting results. This study was designed to determine the association between ACE) gene insertion/deletion (I/D) polymorphism, ACE activity and acute STEMI in Indian population and to determine its influence on outcome after acute MI. Materials and methods: We investigated 934 patients diagnosed with acute STEMI who underwent thrombolysis. ACE I/D polymorphism was detected by polymerase chain reaction and ACE activity was measured in 615 patients. Results: The prevalence of DD, ID, and II genotypes in our study group were 41.97%, 34.36%, and 23.66% respectively. The ACE polymorphism was not significantly associated with the type of myocardial infarction, the LV ejection fraction, the number of vessels diseased and patency of the vessel after thrombolysis. The polymorphism had no influence on in hospital mortality (P = 0.453). The ACE activity also showed no influence on in hospital mortality (P = 0.482). The age > 60 years, Male gender, occluded artery and severe LV dysfunction (LVEF < 35%) were predictors of in-hospital mortality on multivariate regression analysis. Conclusion: There was no differences among ACE (I/D) polymorphism observed in STEMI population. Neither ACE I/D polymorphism nor ACE activity predicted in-hospital mortality inpatients admitted with acute STEMI.